Safe Zone Quantification of the Third Sacral Segment in Normal and Dysmorphic Sacra. Issue 4 (April 2018) - Hwang, John S.; Reilly, Mark C.; Shaath, Mohammad K.; Changoor, Stuart; Eastman, Jonathan; Routt, Milton Lee (Chip); Sirkin, Michael S.; Adams, Mark R.
Abstract : Objective: To quantify the osseous anatomy of the dysmorphic third sacral segment and assess its ability to accommodate internal fixation. Design: Retrospective chart review of a trauma database. Setting: University Level 1 Trauma Center. Patients: Fifty-nine patients over the age of 18 with computed tomography scans of the pelvis separated into 2 groups: a group with normal pelvic anatomy and a group with sacral dysmorphism. Main Outcome Measurements: The sacral osseous area was measured on computed tomography scans in the axial, coronal, and sagittal planes in normal and dysmorphic pelves. These measurements were used to determine the possibility of accommodating a transiliac transsacral screw in the third sacral segment. Results: In the normal group, the S3 coronal transverse width averaged 7.71 mm and the S3 axial transverse width averaged 7.12 mm. The mean S3 cross-sectional area of the normal group was 55.8 mm. The dysmorphic group was found to have a mean S3 coronal transverse width of 9.49 mm, an average S3 axial transverse width of 9.14 mm, and an S3 cross-sectional area of 77.9 mm. Conclusions: The third sacral segment of dysmorphic sacra has a larger osseous pathway available to safely accommodate a transiliac transsacral screw when compared with normal sacra. The S3 segment of dysmorphic sacra can serve as an additional site for screw placement when treating unstable posterior pelvic ring fractures. Abstract : Supplemental Digital Content is Available in the Text.